Livelihood Impact Evaluation of Maintenance and Monitoring of Mangrove Reforestation Initiatives (3MRI) Along Sorsogon Bay - Bongat, Clea L. (Future Science / FSH-PH Publications, 2025)
The over-all objective of the study is to document and evaluate the outcomes of the extension program/project of the Sorsogon State University Specifically, it intends to describe the inputs, activities, outputs, outcomes, and impacts; validate the impact pathway, describe the social, environmental, or economic impact to the beneficiaries; document lessons learned in implementation; and recommend policies for the improvement of the design and replication of the program/project. The project has started on February 2015 in the five (5) coastal barangays of Sorsogon City, namely; Brgy. Rizal, Brgy. Bulabog, Brgy. Bitan-o, Brgy. Buhatan, and Brgy. Talisay. A total of 1,218 beneficiaries along the coastal area barangays were trained and actively involved in the project for the past 5 years with an over-all rating described as better. There are at least 700 mangroves planted in each mentioned coastal areas during the launching of the project with the Head of City Agriculture Office, Mrs. Adeline J. Detera, Student Leaders, and other volunteers. The focus is only Barangay Talisay and the subject for impact evaluation of the project. (2008Primavera, J., & Esteban, J. M. A.) In one of the studies conducted, despite heavy funds for massive rehabilitation of mangrove forests over the last two decades, the long-term survival rates of mangroves are generally low at 10-20%. Poor survival can be mainly traced to two factors: inappropriate species and sites selection.